Biodiversity assessment in the Lower Mekong basin: First record of the genus Oncosclera (Porifera: Spongillina: Potamolepidae) from the Oriental Region - Manconi, Renata; Ruengsawang, Nisit; Ledda, Fabio D.; Hanjavanit, Chutima; Sangpradub, Narumon (Zootaxa, 2012)
Taxonomic richness of Thai Spongillina numbers so far seven species (five genera, one family). The first record of the genusOncosclera Volkmer-Ribeiro, 1970 belonging to the family Potamolepidae Brien, 1967 is here reported with the description ofa new species from the Pong River (NE Thailand, Oriental Region) in the framework of a biodiversity assessment in the LowerMekong Basin. An emended diagnosis of the genus is also provided. The new species, ascribed to the genus Oncosclera fordiagnostic traits of the skeleton and the gemmular architecture, differs from all the other known species of the genus in itsunique combination of diagnostic traits. O. asiatica sp. nov. is characterised by i) more or less alveolate skeleton, ii) conulosesurface with a network of branched subdermal canals, iii) acanthoxeas as dominant megascleres and less frequentacanthostrongyles, iv) gemmular theca sublaminar of compact spongin with a scantly developed pneumatic layer of fibrousspongin, and v) gemmuloscleres as acanthostrongyles from elongated to ovoid with tubercles/spines particularly dense towardsthe tips. Despite the extremely disjunct distribution O. asiatica is morphologically similar to O. intermedia and O. jewelli fromthe Neotropical Region and O. gilsoni from Pacific Islands, from which the former diverges for megascleres and/or gemmuloscleres traits.